Women in Legislature-Representation and Participation Challenges Analysis of Punjab Assembly (2013-2018) - Rashid, Hina (Annals of Human and Social Sciences, 2024)
The study highlights that women's inclusion in decision-making processes is a transformative dynamic that ultimately leads to the Community empowerment. It evaluates the extent of women's representation on decision-making positions and their inclusion in the legislative process, with the focused analysis of Punjab Assembly during the democratic era of 2013-2018. Despite various International measures aimed at enhancing gender parity, women's insufficient representation and inactive participation in political decision-making perpetuates barriers to achieving societal gender equality. The situation in Pakistan remains dire, as entrenched patriarchal structures and many other factors continue to impede women's meaningful participation in decision-making processes. The study adopts mix method approach, utilizing secondary data sources and identifies various factors that constrain women's effective participation. It contends that despite the establishment of reserved seats for women, their substantive engagement in decision-making remains suboptimal. It recommends that certain measures will be helpful to ensure women’s effective and operative role in the legislature, including consensus building between women legislators, their appointment on decision-making positions, and conduction of training regarding parliamentary proceedings.